ANALISIS PIGGYBACK TAX DALAM PENERIMAAN CUKAI HASIL TEMBAKAU (CHT) DI NUSA TENGGARA BARAT - Kumba Digdowiseiso; Priscilia Yolandasari; Mohammad Khairi (Jurnal Ilmiah Global Education, 2023)
The Indonesian government implements a piggyback tax related to cigarette policies. Since January 1, 2014, apart from value-added tax and cigarette excise tax, there is also a cigarette tax imposed on the cigarette industry in Indonesia. This study will explain to what extent and how significant the contribution between piggyback tax and Tobacco Product Excise (CHT) in Indonesia is. This policy was implemented considering the increasingly massive consumption of cigarettes by adults and children. This policy is expected to reduce cigarette consumption in Indonesia. It can also simultaneously increase state revenue. Quantitative descriptive research is the method applied in this study.